Pengaruh Modal, Tenaga Kerja, dan Luasan Lahan terhadap Pendapatan Petani Padi di Desa - Diyah Kusmiyati; Wikan Budi Utami; Suprihati (Nur Science Institute, 2022)
The purpose of this study was to determine the effect of capital, labor, and land area on the income of rice farmers in Brangkal Karanganom Village, Klaten. The type of primary data used in this research is descriptive analysis method, assumption test and hypothesis testing using multiple linear regression analysis. The results of the simultaneous study of the variables of capital, labor, and land area have a positive effect on farmers' rice income in Brangkal Karanganom Village, Klaten, then the results of partial testing of the capital variable on income have no positive and significant effect, then for the labor variable on income produces there is a positive and significant effect of labor on the income of rice farmers and the last is the variable of land area on income there is a positive and significant effect of land area on the income of rice farmers in Brangkal Karanganom Village, Klaten.